Effect of Iron-fortified Wheat Flour on Hemoglobin Levels among Women of Reproductive Age Group in Mansehra, KPK, Pakistan: Iron-fortified wheat flour improves Iron Status - Anis, Riffat Aysha; Anees, Mariam; Zafar, Saira; Farooq, Umar; Abid, Juweria; Akram, Sajeela; Ahmad, Abdul Momin Rizwan (Cellular and Molecular Biology, 2023)
Micronutrient deficiencies continue to affect approximately 25% of the World’s population. Fortification of staple foods is recognized as one of the most effective interventions to combat micronutrient deficiencies such as iron deficiency. The objective of the current research was to elucidate the effect of iron-fortified wheat flour on the mean hemoglobin levels of women of the reproductive age group (15-49 years) in the Mansehra district, KPK, Pakistan. The study sample consisted of 280 women whose baseline hemoglobin levels were determined at the start of the study. They were fed with iron-fortified wheat flour for a period of 120 days after which their hemoglobin levels were measured again. A 24-hour dietary recall was also taken from the study participants to determine the amounts and frequencies of major foods consumed during the last 24 hours. The study results showed that the consumption of iron-fortified wheat flour had significantly increased the mean hemoglobin levels of women. The study concluded that the consumption of iron-fortified wheat flour could be an effective strategy to combat the problem of iron deficiency in Pakistan.